Blockchain Technology as A Means of Wealth Protection (Ḥifẓ al-Māl) in Digital Cryptocurrency Assets: A Maqāṣid-Oriented Analytical Framework - Agus Wahyu Irawan; Muhammad Lathoif Ghozali; Sadiq Ibrahim Mijinyawa; Nurlaili Adkhi Rizfa Faiza (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
The rapid expansion of blockchain technology and digital cryptocurrency assets has generated significant debate within Islamic finance, particularly regarding their compliance with the objectives of Maqāṣid al-Sharīʿah. This study critically examines the role of blockchain technology in the protection of wealth (ḥifẓ al-māl) within digital cryptocurrency assets using a maqāṣid-oriented analytical framework. Employing a qualitative normative–conceptual approach grounded in Jasser Auda’s systems theory of maqāṣid al-Sharīʿah, the study analyzes how core blockchain characteristics transparency, cryptographic security, immutability, and distributed ledger architecture contribute to wealth protection while also identifying inherent risks and limitations. The findings indicate that blockchain can support ḥifẓ al-māl by enhancing transaction accountability, safeguarding ownership, and mitigating fraud. However, such contributions are neither inherent nor unconditional, as they depend on governance structures, regulatory alignment, and ethical usage frameworks. The study further distinguishes between blockchain as a neutral technological infrastructure and cryptocurrency as a financial instrument that may generate Shariah concerns due to volatility, gharar, and speculative excess. By articulating this distinction, the research advances a more proportionate and critically grounded maqāṣid-based assessment of blockchain, contributing to contemporary discourse on Islamic digital finance and offering a conceptual foundation for future regulatory and technological development.